Circulating metabolites as a concept beyond tumor biology determining disease recurrence after resection of colorectal liver metastasis. Issue 1 (January 2022) - Jonas, Jan P.; Hackl, Hubert; Pereyra, David; Santol, Jonas; Ortmayr, Gregor; Rumpf, Benedikt; Najarnia, Sina; Schauer, Dominic; Brostjan, Christine; Gruenberger, Thomas; Starlinger, Patrick
Abstract: Background: Micro-metastatic growth is considered the main source of early cancer recurrence. Nutritional and microenvironmental components are increasingly recognized to play a significant role in the liver. We explored the predictive potential of preoperative plasma metabolites for postoperative disease recurrence in colorectal cancer liver metastasis (CRCLM) patients. Methods: All included patients (n = 71) had undergone R0 liver resection for colorectal cancer liver metastasis in the years between 2012 and 2018. Preoperative blood samples were collected and assessed for 180 metabolites using a preconfigured mass-spectrometry kit ( Biocrates Absolute IDQ p180 kit ). Postoperative disease-free (DFS) and overall survival (OS) were prospectively recorded. Patients that recurred within 6 months after surgery were defined as "high-risk" and, subsequently, a three-metabolite model was created which can assess DFS in our collective. Results: Multiple lysophosphatidylcholines (lysoPCs) and phosphatidylcholines (PCs) significantly predicted disease recurrence within 6 months (strongest: PC aa C36:1 AUC = 0.83, p = 0.003, PC ae C34:0 AUC = 0.83, p = 0.004 and lysoPC a C18:1 AUC = 0.8, p = 0.006). High-risk patients had a median DFS of 183 days versus 522 days in low-risk population (p = 0.016, HR = 1.98 95% CI 1.16–4.35) with a 6 months recurrence rate of 47.6% versus 4.7%, outperforming routine predictors of oncological outcome. Conclusion: Circulating metabolites identified CRCLM patients at highest risk for 6 months disease recurrence after surgery. Our data also suggests that circulating metabolites might play a significant pathophysiological role in micro-metastatic growth and concomitant early tumor recurrences after liver resection. However, the clinical applicability and performance of this proposed metabolomic concept needs to be independently validated in future studies.